2018
DOI: 10.1074/jbc.ra118.001825
|View full text |Cite
|
Sign up to set email alerts
|

Smad4 deficiency impairs chondrocyte hypertrophy via the Runx2 transcription factor in mouse skeletal development

Abstract: Chondrocyte hypertrophy is the terminal step in chondrocyte differentiation and is crucial for endochondral bone formation. How signaling pathways regulate chondrocyte hypertrophic differentiation remains incompletely understood. In this study, using a () gene-deletion approach, we selectively deleted the gene for the signaling protein SMAD family member 4 ( ) in the limbs of mice. We found that the -deficient mice develop a prominent shortened limb, with decreased expression of chondrocyte differentiation mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 69 publications
(86 reference statements)
0
28
0
Order By: Relevance
“…31 Several research groups are investigating the role of Smad4/Runx2 signaling in mediating the cell response to biomaterials. 1,34 Increasing evidence indicates that Smad4/ Runx2 signaling is involved in the responses of cells to Ta NPs. As Smad4 nuclear translocation and accumulation constitute the markers of Smad4/Runx2 signaling activation, 31 we investigated Smad4 and Runx2 protein levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Several research groups are investigating the role of Smad4/Runx2 signaling in mediating the cell response to biomaterials. 1,34 Increasing evidence indicates that Smad4/ Runx2 signaling is involved in the responses of cells to Ta NPs. As Smad4 nuclear translocation and accumulation constitute the markers of Smad4/Runx2 signaling activation, 31 we investigated Smad4 and Runx2 protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…32 Thus, Smad4 expression is mediated by Smad4/Runx2 signaling at the transcriptional level, and Smad4 regulates Runx2 activity and the expression of other osteoblast genes in a feedback loop. 33,34 The cytoskeleton has been shown to control the activation of Smad4/Runx2 signaling in mesenchymal cells upon external stimulation, and cell morphology remodeling and cytoskeletal organization can affect stem cell lineage commitment. 14 Furthermore, the cytoskeletal network allows cells to transfer external mechanical stimuli into the nucleus and activates external stimuli-induced mechanotransduction transducers on the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…8d, e ). Although the result in itself suggests that the Smad transcription factors might directly activate Glut1 gene transcription in response to Bmp, a previous ChIP-seq study failed to detect Smad4 binding in the promoter region (−5kb to +5b around transcription start site) of the Glut1 gene in the embryonic cartilage 27 . We therefore investigated the potential role of mTORC1 signaling due to its known relevance in cellular metabolism and its implication in Bmp signaling 28 .…”
Section: Resultsmentioning
confidence: 73%
“…SOX9 is a master gene in the regulation of chondrogenesis and the maintenance of the chondrocyte phenotype. In contrast, SMAD4 and CBFB are involved in hypertrophic differentiation of chondrocytes [48]. We found that at 14 days of pellet culture, despite maintaining high SOX9 mRNA expression, COL10, RUNX2, and CBFB expression levels were significantly enhanced, indicating that the cells had already begun hypertrophic differentiation.…”
Section: Discussionmentioning
confidence: 69%